2011
DOI: 10.1038/labinvest.2010.177
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic PI3K/Akt signaling by sodium/glucose transporter 1 reduces epithelial barrier damage and bacterial translocation in intestinal ischemia

Abstract: Intestinal ischemia/reperfusion (I/R) causes mucosal barrier damage and bacterial translocation (BT), leading to septic complications. Previous in vitro studies showed that activation of sodium/glucose transporter 1 (SGLT1) prevented the epithelial apoptosis and permeability rise induced by microbial products. Our aim was to investigate whether luminal glucose uptake by SGLT1 protects against ischemia-induced epithelial cell death and barrier dysfunction, and to explore the glucose-mediated cellular survival p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 54 publications
(89 reference statements)
5
68
0
Order By: Relevance
“…5,47 Here, we showed that rats preconditioned to a hypoxic environment displayed a significant reduction in bacterial counts in extraintestinal organs, associated with decreases in transepithelial macromolecular flux and mucosal histopathology on I/R challenge. The attenuation of BT may be attributed to higher barrier integrity and/or stronger antimicrobial effects of phagocytes.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…5,47 Here, we showed that rats preconditioned to a hypoxic environment displayed a significant reduction in bacterial counts in extraintestinal organs, associated with decreases in transepithelial macromolecular flux and mucosal histopathology on I/R challenge. The attenuation of BT may be attributed to higher barrier integrity and/or stronger antimicrobial effects of phagocytes.…”
Section: Discussionmentioning
confidence: 82%
“…45,46 Magnetic Resonance Imaging (MRI)-Based Intestinal Permeability Assay To assess the intestinal permeability in vivo, Gadodiamide (Gd)-containing contrast solution (Omniscan; GE Healthcare, USA) was instilled into the lumen of a ligated intestinal sac (10 cm) to a final concentration of 0.25 M immediately after the release of the artery clamp in I/R rats, and the signal intensity of this reagent in the plasma was quantified as described previously. 5,47 The intestinal sac was created 1 cm proximal to the cecum by thread ligature and a PE-10 tube was intubated to one end of the sac for instillation of Gd solution. In sham-operated animals, the Gd probe was injected into the intestinal sac after mock manipulation.…”
Section: Analysis Of Bacterial Counts In Intestines and Extraintestinmentioning
confidence: 99%
See 2 more Smart Citations
“…Primary antibodies included mouse antihuman PCNA (1:2,000), phospho (p)-and total (t)-IkB (1:2,000), p-and t-ERK1/2 (1:4,000), p-and t-JNK (1:2,000), p-and t-Akt (1:2,000), p-PKCz (Thr410; 1:2,000), p-PKCz (Thr560; 1:5,000; Abcam Epitomics), t-PKCz (1:2,000), p-tyrosine (1:2,000; EMD Millipore), CD14 (1:50 for immunofluorescence and 1:2,000 for Western blot; R&D Systems), TLR4 (1:100 for immunofluorescence and 1:2,000 for Western blot; Santa Cruz Biotechnology), TLR2 (1:2,000; Santa Cruz Biotechnology), MyD88 (1:2,000), bromodeoxyuridine (BrdUrd; 1:200; Abcam), mouse IgG1 and IgG2a isotype controls (R&D Systems), rat IgG2a isotype controls (Abcam), and b-actin (1:10,000; Sigma; refs. 19,31). The secondary antibodies used were goat anti-mouse IgG conjugated to horseradish peroxidase (1:2,000), and to Alexa 594 or 488 (1:1,000; ThermoFisher).…”
Section: Antibodiesmentioning
confidence: 99%